Piper betle L. leaf extracts inhibit quorum sensing of shrimp pathogen Vibrio harveyi and protect Penaeus vannamei postlarvae against bacterial infection - John Paul Matthew D. Guzman (2022)
Vibriosis, including the luminescent shrimp disease and acute hepatopancreatic necrosis disease (AHPND), with Vibrio harveyi as one of their causative agents, is a major shrimp disease causing huge economic losses in the Philippines, Thailand, Vietnam and other Southeast Asian countries. It is induced through the formation of biofilm as a result of bacterial cell-to-cell communication or quorum sensing (QS). Hence, this mechanism may be used as a target for bioactive compounds in controlling V. harveyi infections in shrimp. In this study, crude ethanolic extract (CE) and crude alkaloids (CA) from Ikmo (Piper betle L.), a plant native to Southeast Asia, were observed to significantly (p < 0.05) inhibit biofilm formation of wild-type strains V. harveyi VH0, VH1 and BAA-1116 in chitosan-coated microtiter plates without inhibiting their growth. Confocal laser scanning microscopy revealed thinner biofilms formed upon treatment with both extracts. Furthermore, both CE and CA significantly (p < 0.05) inhibited bioluminescence in QS reference strain V. harveyi BAA-1116 and was found to interfere with QS by modulating autoinducer (AI) activities as observed in both phenotypic and gene expression analyses. Both extracts also did not negatively affect shrimp growth and pre-infection mortality rate. Despite the in vitro results however, in vivo analysis showed that only P. betle CE, when supplemented to shrimp feed, protected Penaeus vannamei postlarvae against V. harveyi infection after seven days. These suggest the potential supplementation of shrimp feed with P. betle crude extract as protection against Vibriosis.